2003
DOI: 10.1002/dmrr.390
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate metabolism in normal pregnancy and in gestational diabetes

Abstract: Complex though integrated hormonal and metabolic changes characterize pregnancy. In the face of progressive decline in insulin action, glucose homeostasis is maintained through a compensatory increase in insulin secretion. This switches energy production from carbohydrates to lipids, making glucose readily available to the fetus. This precise and entangled hormonal and metabolic condition can, however, be disrupted and diabetic hyperglycemia can develop (gestational diabetes). The increase in plasma glucose le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
286
1
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(313 citation statements)
references
References 138 publications
9
286
1
17
Order By: Relevance
“…However, for the triglyceride there was a steep rise from the control to the third trimester value with a non-mirror image decrease at the postpartum period. 17 Overall, the physiological mechanism in the postpartum period for return of the elevated lipid profile to pre-pregnant value is optimum. Some studies have also revealed that the mean values of serum TC, TG, and LDL are significantly higher among the hypertensive patients in comparison to normotensive.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the triglyceride there was a steep rise from the control to the third trimester value with a non-mirror image decrease at the postpartum period. 17 Overall, the physiological mechanism in the postpartum period for return of the elevated lipid profile to pre-pregnant value is optimum. Some studies have also revealed that the mean values of serum TC, TG, and LDL are significantly higher among the hypertensive patients in comparison to normotensive.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the increased tolerance of natural protein during the later stages of the pregnancy was predicted as the requirements of the fetus grow considerably during this time and maternal physiology changes to accommodate this. Other endocrine changes during pregnancy promote insulin resistance and an anabolic state (Di Cianni et al 2003), also allowing increased protein tolerance. Careful monitoring was also required in the post-partum period.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational steroid hormones and placental lactogen induce peripheral insulin resistance and enhance foetal nutrition by diverting glucose, fatty acids and amino acids from maternal to foetal tissues 6 . Diabetes results when the pancreatic -cells fail to cope with the increased demands for insulin.…”
Section: Maternal Diabetes and Foetal Growth -Fuelmediated Teratogenesismentioning
confidence: 99%